2014
DOI: 10.1186/2251-6832-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of solar radiation on diversely oriented surfaces and optimum tilts for solar absorbers in Malaysian tropical latitude

Abstract: This study describes the results of a "well-to-wheel" life cycle assessment (LCA) carried out to determine the potential greenhouse gas and criteria pollutant emission reductions that could be achieved by converting associated flare gas directly to synthetic fuels at oil wellheads in the US and globally. A Greyrock Flare Gas-to-Fuels™ conversion process at an Ohio oil well was used as the base case for this LCA. The liquid fuel produced directly from associated gas is comprised primarily of premium synthetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Optimum fixed-collector positions based on mathematical models of solar resource are available for countries such as Lesotho [4], Cyprus [5], Egypt [6], Brunei Darussalam [7], China [8], Iran [9], the western Himalayas [10], India [11] and Malaysia [12]. Estimation and optimization of the incident solar radiation on tilted surfaces can also be determined using different empirical models [13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimum fixed-collector positions based on mathematical models of solar resource are available for countries such as Lesotho [4], Cyprus [5], Egypt [6], Brunei Darussalam [7], China [8], Iran [9], the western Himalayas [10], India [11] and Malaysia [12]. Estimation and optimization of the incident solar radiation on tilted surfaces can also be determined using different empirical models [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Christensen and Barker [24] presented such contour plots for different locations in the United States of America using solar data based on mathematical models. Ng et al [12] presented similar contour plots based on mathematical models for Malaysia. Li and Lam [25] also presented contour plots for Hong Kong, but these were based on measured solar data.…”
Section: Introductionmentioning
confidence: 99%
“…So, the results of this work are in a good agreement with those of Uba & Sarsah (2013) for the first and third periods while the result of Uba & Sarsah (2013) should be corrected for the second period because 1) the solar collector should be orientated to the North during April -August period and 2) the proposed value is too high. Ng et al (2014) found, for Bangi, Malaysia (L = 3° N), that Bopt,m = 22, 16, 5, -8, -18, -22, -21, -11, 0, 11, 19, 24 for January to December respectively. When calculating Bopt,m for theses months using the proposed methodology of this work one obtains that Bopt,m = 33.5°, 23.1°, 7.2°, -11.9°, -25.5°, -31.2°, -28.5°, -17.4°, -5.6° (12) Table 6) it was found that the results of (O) set of equations are not compatible with other results and they could not be justified.…”
Section: Collector Optimum Tilt Over a Periodmentioning
confidence: 99%
“…Oko and Nnamchi (2012) studied theoretically the optimum tilt angle for low latitudes, 4.86-13.02 o N, spanning the territory of Nigeria and expressions for the optimum tilt angles with respect to the low latitudes were also provided. Ng et al (2014) found that the optimum angles for seasonal south-and north-facing surfaces are 14.4° and 14.8°, respectively. Kamanga et al (2014) mentioned that for Zomba district there are only two seasonal adjustments that are needed for PV solar panels and these should be carried out at the end of February and at the end of September.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies exist on the topic of placement and orientation of PV panels on roofs, facades or the ground, but solely taking into account flat modules on planar surfaces [1][2][3][4][5]. With the increased availability of flexible thin-film PV panels in recent years, the application of PV panels on curved surfaces becomes feasible, thus broadening the application potential of photovoltaic modules.…”
Section: Introductionmentioning
confidence: 99%